How variable are the journal impact measures?. Issue 6 (9th September 2014) - David Stuart, Dr; Haghdoost, Aliakbar; Zare, Morteza; Bazrafshan, Azam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the variability of the impact factor (IF) and additional metrics in biomedical journals to provide some clues to the reliability of journal citation indicators. Design/methodology/approach – Having used ISI Journal Citation Reports, from 2005 to 2011, the authors extracted 62 subject categories related to biomedical sciences. The category lists and citation profile for each journal were then downloaded and extracted. Coefficient of variation was applied to estimate the overall variability of the journal citation indicators. Findings – Total citation indicators for 3, 411 journals were extracted and examined. The overall variability of IFs and other journal citation measures in basic, clinical or translational, open access or subscription journals decreased while the quality and prestige of those journals developed. Interestingly, journal citation measures produced dissimilar variability trends and thus highlighted the importance of using multiple instead of just one measure in evaluating the performance and influence of biomedical journals. Eigenfactor™, Article's Influence and Cited Half Life proposed as more reliable indicators. Originality/value – The relative variability of the journal citation measures in biomedical journals would decrease with a development in the impact and quality of journals. Eigenfactor™ and Cited Half Life are suggested as more reliable measures indicating few changes during the study period and across different impact level journals. These findings will be useful for librarians, researchers and decision makers who need to use citation measures as evaluative tools.